الفرقة المسيحية الدوناتية في شمال إفريقيا - محمد علي, نيس (جامعة الوادي university of eloued, 2019)
إن الهدف من هذه الدراسة عن المذهب الدوناتي المسيحي في شمال أفريقيا بالأول معرفة عن تاريخ المنطقة الديني وإظهار بداية أول كفاح ديني ضد المستعمر سياسيا وإيقاف لظلم الكاثوليكية التي تحاول السيطرة بعقائدها. و هذه الدراسة توضح تمسك البربر الأمازيغ والدوناتيين بمذهبهم والرد على من يحاول تشويهها والعبث بها وذلك رغما عما عاناه البربر الدوناتيين من ظلم ديني وعرقي ومذهبي. وفيها أيضا توضيح بما يخص القديس أغسطين كذلك بأحقية التمجيد إذا كانت له أم للدوناتيين الأحرار وبما وصفهم . وقد قسمنا الدراسة إلى ثلاث مباحث نحاول فيها جهدنا للإجابة عن الإشكاليات المطروحة أول الرسالة. ونسأل الله العون والسداد المقدمة ز الترجمة The purpose of this study on the Christian Donatian doctrine in North Africa is first to learn about the history of the religious region and to show the beginning of the first religious struggle against the colonizer politically and to stop the injustice of the Catholic Church which is trying to control its doctrines . This study demonstrates the adherence of the Amazigh Berbers and the response to those who attempt to distort and tamper with it, despite the suffering of the Donner Berbers from religious. It also contain an exposition of St.Augustine as well as the right to glorify him if he was the mother of the Free Donuts and what he described. We have divided the study into three studies in which we try our best to answer the problems presented in the first research . We ask Allah help and repayment
ليسانس